Pathogenesis of Chicken Astrovirus Related Illnesses - Raji, Abdullahi Abdullahi; Omar, Abdul Rahman (Frontiers in Veterinary Science, 2022)
Of the several known viruses, chicken astrovirus (CAstV) has been associated with diarrhea, runting stunting syndrome, severe kidney disease and gout, and white chick syndrome (WCS) in young broiler chicks. Discovered in 2004, CAstV consists of two genogroups with an expanding subgroup because of the diversity exhibited in its viral capsid sequence. Despite this, there exists a dearth of knowledge in its pathogenesis. This review highlights the pathogenesis and development of in-vivo and in-vitro models.